THE PHENOMENA OF VIOLENCE AGAINST WOMEN AS A HUMAN RIGHTS VIOLATION: VIOLENCE EXPERIENCES OF A GROUP OF WOMEN LIVING IN WOMEN’S SHELTER - Fadime SEÇGİN; Mehmet TATAN (International Journal of Eurasia Social Sciences, 2017)
Violence against women is a common multidimensional infraction in the world and Turkey. Both international instutions and various organizations in Turkey has been doing projects to solve this infraction causing women to be hurt and injured psycologically and physically, and also causing them pain, insulting them, keeping discrimination againist women and preventing their main rights and freedom. But unfortunately, this infraction of human rights can’t be prevented.This research shows that whether women staying at women’s shelter perceive the violance as an infraction of humanrights or not, what kind of violence they are exposed to, by whom they are exposed to violence, the reasons of being exposed to violence, their reactions to the violence, what kind of a support they get after being exposed to violence. The group of research consisits of 8 voluntary women who were somehow exposed to violence and stay at women’s shelter in Tokat. The research is case study among qualitative research models. During the data collection, semi-structured interview form has been used. Descriptive analysis was applied to analyze the data. While analyzing the data, the answers given by participants have been studied deeply and participants’ direct expressions have often been used.This research shows that the participants have been mostly exposed to physical, verbal and economical violence. According to participants, the violence exposed to themselves have been perceived it as a problem which is an infraction of their main rights, and which ignores their personality rights and imperils themselves seriously. Many participants told that their parents, friends and relatives left them alone in their struggle with violence; therefore, they stated that they had difficulties in coping with the violence., same difficulties to prevent the violence. Women are exposed to violence not only by men but aso by women. Furthermore, women stated that they applied official agencies not before they were exposed to violence but rather when the violence was no more irresistable.